2011
DOI: 10.1111/j.1399-0012.2011.01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Over 500 pancreas transplants by a single team in São Paulo, Brazil

Abstract: Pancreas transplantation (PT) remains a developing practice in Latin America. From 1996 to 2009, 506 PTs were performed by our team in the following categories: simultaneous pancreas-kidney (SPK), simultaneous deceased donor pancreas and living-donor kidney (SPLK), pancreas after kidney (PAK), and pancreas transplant alone (PTA). Enteric drainage was preferred for SPK and bladder drainage for solitary PT or SPLK. Immunosuppression was with tacrolimus, mycophenolate mofetil, and steroids, and anti-lymphocytic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…One-year cumulative patient survival was 82%. Pancreas and kidney survival rates were 70% and 78% after 1 year, respectively [14].…”
Section: Discussionmentioning
confidence: 99%
“…One-year cumulative patient survival was 82%. Pancreas and kidney survival rates were 70% and 78% after 1 year, respectively [14].…”
Section: Discussionmentioning
confidence: 99%
“…23 Unfortunately, the largest SPLK series in the literature have not been powered enough to demonstrate a survival difference between SPLK and SPK transplants. 24,25 In our series, we examined outcomes between SPK and SPLK transplants and found that SPK pancreata had improved survival and decreased rejection episodes over SPLK pancreata in bivariate and multivariable analyses. Furthermore, SPLK and PAK pancreata still had a survival advantage over PTA pancreata, suggesting that a homologous kidney-pancreas origin may prove advantageous in the combined organ transplant.…”
Section: Discussionmentioning
confidence: 99%
“…To address the second hypothesis, we explored the observation that SPLK transplants seem to yield a lower pancreas graft survival 23 . Unfortunately, the largest SPLK series in the literature have not been powered enough to demonstrate a survival difference between SPLK and SPK transplants 24,25 . In our series, we examined outcomes between SPK and SPLK transplants and found that SPK pancreata had improved survival and decreased rejection episodes over SPLK pancreata in bivariate and multivariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Death-censored dual graft loss, ascribed to acute and chronic rejection, was three times more likely in AA (21%) versus Caucasian patients (7%, p = 0.0055). Several single center studies from South America have reported good outcomes in a predominantly Hispanic population, while other studies from China, Korea, India, and Japan have reported excellent outcomes in a predominantly Asian population [48,50,[144][145][146][147][148]. In 1997, the University of Miami group published one of the first reports of successful SPKT in Hispanic recipients with T1DM [144].…”
Section: Pancreas Transplantation In Minoritiesmentioning
confidence: 99%